2017
DOI: 10.1007/s10040-017-1675-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical constraints between the karst Tabular Middle Atlas Causses and the Saïs basin (Morocco): implications of groundwater circulation

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…During periods of intense rainfall, water turbidity is observed [36], reducing water quality. This turbidity can be attributed internally to the leaching of the karstic network in which meteoric water circulates, and also externally, at the level of infiltration within different karst landforms [7,41].…”
Section: Geological and Geomorphological Overview Of The Middle Atlasmentioning
confidence: 99%
See 1 more Smart Citation
“…During periods of intense rainfall, water turbidity is observed [36], reducing water quality. This turbidity can be attributed internally to the leaching of the karstic network in which meteoric water circulates, and also externally, at the level of infiltration within different karst landforms [7,41].…”
Section: Geological and Geomorphological Overview Of The Middle Atlasmentioning
confidence: 99%
“…Among these karst landforms, collapse and cover-subsidence dolines and dissolution sinkholes have been identified as a source of environmental and geo-hazards risks. Chemical analysis performed on water springs located in the junction of the TMA and Saïs Basin [7][8][9][10] revealed that, during periods of high precipitation, the degradation of water quality is linked to superficial pollutants infiltrated into reservoirs through sinkholes located in agricultural areas, thus resulting in the internal gradual erosion of karst systems. The pesticides, herbicides and chemical fertilizers used in farming and agricultural production percolate into the groundwater aquifer and consequently change the composition, color and the taste of water springs.…”
Section: Introductionmentioning
confidence: 99%
“…Around this area, Strombolian cones show a slightly higher elevation, but phreatomagmatic centres are generally located in a lower eastward area, which can be much closer to the shallow water table. The widespread karstic-carbonate rock layers combined to heavy precipitations as rain and as snow, make of the tabular Middle-Atlas an abundant groundwater sources (Amraoui 2004, Martin 1981, Miche et al 2018, regarded as a great water tower and hydrological regulator in Morocco (Bentayeb, Leclerc 1977, Peyron 1980, Menjour et al 2017. Generally, the Strombolian dynamic activity is dominant consisting of 66% of volcanic events.…”
Section: Geologic and Geomorphologic Setting Of The Study Areamentioning
confidence: 99%
“…In Morocco, the Tabular Middle Atlas Causses reservoir is the main drinking water supply of Fez-Meknes region. However, in rainfall periods their water quality is impaired, due to a strong turbidity [2]. This phenomenon is well known in karstic springs and can make the water unfit for consumption [3].…”
Section: Introductionmentioning
confidence: 99%